Bullying among students ecological insights from a school based adolescent health survey, Himachal Pradesh, India - Deepika Bahl; Devika Mehra; Nikita Patel; Saroj Mohanty; Subha Sankar Das; Rishi Garg; Gaurav Sethi; Anjali Chauhan; Sunil Mehra (PLoS ONE, 2026)
Background and objective Bullying among adolescents is a growing public health concern with serious mental, emotional, and social well-being consequences. This study aims to assess prevalence of physical and cyberbullying among school-going adolescents (13–17 years) in Himachal Pradesh, India, and identify risky and protective factors using an ecological framework descriptively. Methods A cross-sectional, school-based survey was conducted across Himachal Pradesh using culturally adapted standardised questionnaire. Multivariate logistic regression analysis was performed to identify factors associated with bullying perpetration and victimization. Results Out of 7563 adolescents surveyed, 18.41% reported involvement in physical or cyber bullying, with 13.96% involved in physical bullying and 9.64% in cyberbullying. Additionally, 15.60% adolescents reported being victims, including 11.40% experiencing physical and 7.88% cyberbullying. Associated Perpetration factors : • Behavioral factors : Increased risk was associated with junk food consumption, skipping breakfast, substance use, sexual activity, excessive screen time (>8 hours/day), and involvement in physical fights. • Emotional factors : Feelings of hopelessness and nervousness were associated with increased odds of both physical and cyberbullying. • Family-related factors : Adolescents with unskilled parents had higher odds of bullying others, while strong parental connectedness showed significant positive association. Victimization • Demographic and behavioral factors : Boys and adolescents from urban areas were more likely to be victims. Additional associated factors included unhealthy eating habits, substance use and sexual activity. • Emotional factors : Feelings of disappointment and distress were associated with increased victimization • Family-related factors : Parental connectedness was protective against both forms of bullying. Conclusion Findings highlight significant prevalence of both physical and cyberbullying among adolescents in Himachal Pradesh, with distinct behavioral, emotional, and family-related risk factors. Parental connectedness proved protective, underscoring the need for integrated, multi-level interventions to foster healthier behaviors, emotional well-being, and safer schools. Ayushman Bharat School Health and Wellness Programme can be strengthened by tailoring its module based on the identified risk and protective factors.